2015
DOI: 10.1590/s1806-66902015000100019
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive phytochemicals and antioxidant activity in fresh and dried lychee fractions1

Abstract: -Fruit of the lychee cv. Bengal are approximately 50% peel and seeds, which are discarded. These byproducts have antioxidant compounds which are capable of blocking the harmful effects of free radicals in the body. Bioactive compounds (ascorbic acid, beta-carotene, lycopene and phenols) and antioxidant activity were evaluated in different extracts, both fresh and dried at 45 °C, of the skin, pulp and seeds of the lychee, which were subjected to principal component analysis to clarify which of the compounds are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 25 publications
0
11
0
3
Order By: Relevance
“…For instance, Queiroz et al (2015) reported the litchi antioxidant capacity of 47.92% for aqueous extract, 27.67% for acetone extract, 39.12% for the extract with 70:30 (v/v) acetone:ethanol and 78.42% for the methanol extract. It can be stated that n-butane has better ability to extract compounds with antioxidant activity than water, ethanol and acetone, while methanol is equivalent.…”
Section: Determination Of Antioxidant Activity Of Oat and Litchi Extrmentioning
confidence: 99%
“…For instance, Queiroz et al (2015) reported the litchi antioxidant capacity of 47.92% for aqueous extract, 27.67% for acetone extract, 39.12% for the extract with 70:30 (v/v) acetone:ethanol and 78.42% for the methanol extract. It can be stated that n-butane has better ability to extract compounds with antioxidant activity than water, ethanol and acetone, while methanol is equivalent.…”
Section: Determination Of Antioxidant Activity Of Oat and Litchi Extrmentioning
confidence: 99%
“…Polyphenolic compounds with ortho-diphenolic structure are abundant in litchi pericarp. Flavonoids and anthocyanins, like procyanidin B2, B4, epicatechin, cyanidin-3-retinoside, cyanidin-3-glucoside, quercetin-3-retinoside and quercetin-3-glucoside constitute significant percentage of bioactive principles of litchi pericarp (Queiroz et al, 2015;Lin et al, 2013;Wang et al, 2006). Phenolic constituents of litchi pup may exist in free or bound form and their composition depends greatly on selection of proper extraction solvent mixture.…”
Section: Litchimentioning
confidence: 99%
“…The peel and seed are rich in antioxidants such as ascorbic acid, phenolic compounds including gallic acid, flavonoids (procyanidin B4, procyanidin B2 and epicatechin) and anthocyanins (cyaniding 3-rutinoside, cyanidin-3-glucoside, quercetin3-rutinoside and quercetin 3-glucoside). Pharmacological studies indicate that the by-products of the lychee have various effects including anti-inflammatory, anti-hyperlipidemic, anti-hyperglycemic, hepatic and cardioprotective, as well as having high antioxidant activity [7].…”
Section: Introductionmentioning
confidence: 99%